Evaluating image classification techniques on ASTER data for lithological discrimination in the Barberton Greenstone Belt, Mpumalanga, South Africa - Kemp, Jacobus Nicholas; Zietsman, H. L.; Stevens, G. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Geography and Environmental Studies))--University of Stellenbosch, 2005.